Answered

Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

If 3t-7 = 5t then 6t =
How do I solve this?  I've tried finding help online, but I'm getting more confused.



Sagot :

[tex]3t-7=5t\ \ \ /+7\\\\3t-7+7=5t+7\\\\3t=5t+7\ \ \ /-5t\\\\3t-5t=5t-5t+7\\\\-2t=7\ \ \ /:(-2)\\\\t=-\frac{7}{2}\\\\\\6t=6\cdot(-\frac{7}{2})=3\cdot(-7)=-21[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.